Treatment patients with musculoskeletal chest wall pain using standard and complex therapy - Aleksey N. Barinov; Evgeniya V. Iakovleva (Consilium Medicum)
Background. Nonsteroidal anti-inflammatory drugs, muscle relaxants, massage, physiotherapy procedures (standard therapy –ST) are widely used in chronic the chest wall pain syndrom (CWPS). Complex therapy (CT) is more effective with CWPS, including additionally personalized kinesiotherapy, psychological treatment methods and the introduction of anesthetics and corticosteroids into the area of identified sources of pain. There are few studies comparing the effectiveness of standard and complex therapy in CWPS, which was the purpose of our study.